Nanoemulsions as delivery systems of hydrophobic silybin from silymarin extract: Effect of oil type on silybin solubility, in vitro bioaccessibility and stability. Issue 1 (September 2015) - Calligaris, Sonia; Comuzzo, Piergiorgio; Bot, Francesca; Lippe, Giovanna; Zironi, Roberto; Anese, Monica; Nicoli, Maria Cristina
Abstract The potential of nanoemulsion delivery systems to carry silybin from silymarin extract was studied. To this purpose, sunflower oil, extra virgin olive oil and castor oil were used to prepare silymarin loaded nanoemulsions. The effect of oil type on the silybin solubility and in vitro bioaccessibility was evaluated. Moreover, the changes in particle size, silybin concentration, oxygen consumption and hydroperoxide concentration were studied in nanoemulsions during storage at 20 °C. Results showed that silybin can be successfully incorporated into physically stable nanoemulsions prepared with the different oils. The oil type slightly influenced the silybin in vitro bioaccessibility, while it affected the nanoemulsion particle size as well as silybin stability during storage. In particular, silybin underwent degradation, showing lower stability in extra virgin oil and sunflower oil than in castor oil. Results also showed that the presence of the silymarin extract containing silybin did not affect the oxidation kinetics of the carrier oils.